High stakes - Snodgrass, Melinda M., 1951-; Durham, David Anthony, 1969-; Leigh, Stephen; Miller, John J., 1954-; Spector, Caroline; Tregillis, Ian (Wild cards., 2016)
Officer Francis, vigilante joker "The Infamous Black Tongue," and ace thief Tesseract are forced by a cold-blooded Baba Yaga into an illegal fight ring as part of her effort to placate a vicious monster from another dimension.